2004
DOI: 10.1016/s0014-5793(04)00246-7
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins are powerful inducers of NGF and BDNF production in mouse astrocyte cultures

Abstract: We found that prostaglandin (PG) D 2 and PGE 2 , which are major PGs in the brain of mammals, powerfully induced the secretion of nerve growth factor (NGF) from cultured mouse astrocytes; PGE 2 or PGD 2 induced an approximately 12-or 19-fold increase in NGF secretion after a 24-h incubation, respectively. Moreover, it was found that the sequential metabolites of PGD 2 , PGJ 2 , v v 12 -PGJ 2 , and 15-deoxy-v v 12;14 -PGJ 2 , induced the NGF secretion to the culture medium strikingly (60^98-fold of the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 36 publications
2
56
0
Order By: Relevance
“…Elmariah et al (2004) found GABA A receptor clustering in response to BDNF through Trk-B receptors. Astroglia that we added are also known to produce BDNF in response to activitydependent trans-synaptic signals from prostaglandins (Toyomoto et al, 2004). Together with integrin-mediated astroglial adhesion to neurons, these prostaglandins activate protein kinase C signaling in neurons and excitatory synaptogenesis (Hama et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Elmariah et al (2004) found GABA A receptor clustering in response to BDNF through Trk-B receptors. Astroglia that we added are also known to produce BDNF in response to activitydependent trans-synaptic signals from prostaglandins (Toyomoto et al, 2004). Together with integrin-mediated astroglial adhesion to neurons, these prostaglandins activate protein kinase C signaling in neurons and excitatory synaptogenesis (Hama et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PGD 2 induces nerve growth factor and brain-derived neurotrophic factor (Toyomoto et al 2004). In addition, a study by Andreasson's group showed that the DP1 agonist BW245C increases the level of cAMP and protects hippocampal slice cultures against N-methyl-D-aspartic acid (NMDA)-induced excitotoxicity (Liang et al 2005).…”
mentioning
confidence: 99%
“…PGs are produced as a result of cyclooxygenase (COX) activity and modulate cerebral blood flow regulation, synaptic transmission, neurotrophin production, angiogenesis, gene expression and can change such biological processes like pain perception, body temperature and sleep/awake cycle (Ahmadi et al, 2002;Kunz et al, 2006;Urade and Hayashi, 1999;Toyomoto et al, 2004;Chen et al, 2002;Chen and Bazan, 2005;Zhu et al, 2006). In addition, many studies have attested to the importance of brain PGs in the development of Alzheimer's disease, stroke, brain inflammation, traumatic brain injury and neurodegenerative diseases Bazan et al, 1995;Minghetti, 2004).…”
Section: Introductionmentioning
confidence: 99%